2021
DOI: 10.1016/j.bj.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum bilirubin levels and progression of albuminuria in Taiwanese with type 2 diabetes mellitus

Abstract: Background To investigate the association between serum bilirubin (BIL) levels and the progression of albuminuria in type 2 diabetic Taiwanese. Methods Longitudinal data from January 2001 to June 2015 were retrospectively reviewed from Chang Gung Memorial Hospital in Taiwan. A total of 2877 type 2 diabetic patients with normal total BIL levels were divided into 4 groups according to BIL, with the highest BIL in the fourth group. The urinary albumin/creatinine ratio (UAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Interestingly, although some studies demonstrated a negative association between STB levels and the incidence and progression of CKD in T2DM subjects, 27,28,30 when distinguishing UCB from STB, the conclusion of the relationship between UCB and CKD was disputable in T2DM patients and the relevant studies were sparse. For example, a longitudinal observational study in T2DM subjects found that the subjects with the lowest STB levels (0.1–0.3 mg/dl) had the highest risk of developing CKD stage 3, and SB did not exceed 1.2 mg/dl in all subjects in this study 30 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, although some studies demonstrated a negative association between STB levels and the incidence and progression of CKD in T2DM subjects, 27,28,30 when distinguishing UCB from STB, the conclusion of the relationship between UCB and CKD was disputable in T2DM patients and the relevant studies were sparse. For example, a longitudinal observational study in T2DM subjects found that the subjects with the lowest STB levels (0.1–0.3 mg/dl) had the highest risk of developing CKD stage 3, and SB did not exceed 1.2 mg/dl in all subjects in this study 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although some studies demonstrated a negative association between STB levels and the incidence and progression of CKD in T2DM subjects, 27,28,30 when distinguishing UCB from STB, the conclusion of the relationship between UCB and CKD was disputable in T2DM patients and the relevant studies were sparse.…”
Section: Association Of Serum Ucb Levels and Quintiles With Ckdmentioning
confidence: 99%
See 3 more Smart Citations